Palatomaxillary Reconstruction: Fibula or Scapula - Badhey, Arvind K.; Khan, Mohemmed N. (Seminars in Plastic Surgery, 2020)
Palatomaxillary reconstruction presents a unique challenge for the reconstructive surgeon. The maxillofacial skeleton preserves critical aerodigestive functions—it provides a stable hard palate to support mastication and separate the nasal and oral cavities, and buttress support to provide adequate midface contour. Free tissue transfer has become a routine part of the reconstructive ladder in managing palatomaxillary defects. While there is a wide variety of options for bony reconstruction within the head and neck, the fibula and the scapula, and their variations, have become two of the most commonly used options for midface reconstruction. This review will discuss the advantages and disadvantages of both in specific regard to reconstruction of the palatomaxillary area.
Keywords: palatomaxillary reconstruction; microvascular reconstruction; fibula free flap; scapula free flap